Trends on Carbon Footprint and Climate Change Research: A Bibliometric Study from 2000 to 2022 - Faten Ellouz; Amal Barkouti (African Journal of Advanced Pure and Applied Sciences, 2023)
In recent years, global scientific interest in Carbon Footprint (CF) analysis to mitigate Climate Change (CC) has significantly increased. The present work aims to apply a bibliometric study in order to analyze the research trends in the field of carbon footprint and their contributions in climate change during the period 2000-2022. Our analysis based on the WoS database, based on 3459 articles, and revealed that scientific research on carbon footprint and their contributions in climate change is a relatively recent thematic of research which appeared in the last two decades. Although the number of publications has grown over the years, scientific production is still limited and evolves much slower in many countries. USA, China, UK, Australia and Germany are the leading research production in this field totalizing together over 60% of the total scientific production. The main topics addressed in the scientific literature under this thematic are related to life cycle assessment followed by greenhouse gases emissions and sustainable development.